THE REFLECTION OF NILSS GRĪNFELDS PERSONALITY IN THE MATERIALS OF HIS ARCHIVE (Mūzikas akadēmijas raksti, 2024)
August 11 of 2007 witnessed the one hundredth anniversary since birth of Nilss Grīnfelds, a pianist, composer, musicologist and teacher. His creative life was spent under the Soviet regime. He was the promulgator of its ideology but at the same time, owing to his erudition and knowledge, he proved to be an authority for many musicians. That was the time when every single composer and musicologist of Soviet Latvia had to pay charge to the Soviet political system and it was done. The present paper has resulted from the investigation of Grīnfeld’s family archive, presented to the department of music of the Riga Museum of Literature, Theatre and Music (Rakstniecības, teātra un mūzikas muzejs) by Zigrīda Grīnfelde, the composer’s spouse. The archive contains more than 2000 units, among them different documents, photographies, correspondence, manuscripts and publications, enabling scientists to disclose hitherto little known pages in the development of Grīnfeld’s creative personality.